2016
DOI: 10.1038/ncb3406
|View full text |Cite
|
Sign up to set email alerts
|

Self-repair promotes microtubule rescue

Abstract: SummaryThe dynamic instability of microtubules is characterised by slow growth phases stochastically interrupted by rapid depolymerisations called catastrophes. Rescue events can arrest the depolymerisation and restore microtubule elongation. However the origin of these rescue events remain unexplained. Here we show that microtubule lattice self-repair, in structurally damaged sites, is responsible for the rescue of microtubule growth. Tubulin photo-conversion in cells revealed that free tubulin dimers can inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
214
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(238 citation statements)
references
References 49 publications
8
214
1
2
Order By: Relevance
“…The cell’s careful control in defect removal suggests that defects impact microtubule-based processes. This is corroborated by a recent study that sheds new light on the biological effect of defects on the dynamic instability of microtubule growth30. Here, we seek to understand the effect of microtubule defects on motor-based intracellular transport.…”
mentioning
confidence: 61%
“…The cell’s careful control in defect removal suggests that defects impact microtubule-based processes. This is corroborated by a recent study that sheds new light on the biological effect of defects on the dynamic instability of microtubule growth30. Here, we seek to understand the effect of microtubule defects on motor-based intracellular transport.…”
mentioning
confidence: 61%
“…Because microtubules are very stiff polymers that rupture when subjected to flexural stresses (13), this highly bent morphology suggests the existence of protective mechanisms for long-lived microtubules. The repair of lattice defects has emerged as an intrinsic property of microtubules that are subjected to mechanical stress (14, 15) and acetylation protects microtubule from mechanical fatigue in vitro (4). Further suggesting that acetylation may confer mechanical protection to microtubules, removing TAT-1 from touch receptor neurons of nematodes results in profound microtubule lattice defects (6, 16) that can be rescued by paralyzing the animals (8).…”
Section: Main Textmentioning
confidence: 99%
“…28, 29 When the free tubulin associates within the lattice defect, it is in the GTP form, in the straight conformation. 29 The healed site becomes mechanically and chemically more stable.…”
Section: Non-equilibrium Aspects Of the Assembly Of Tubulin Into Micrmentioning
confidence: 99%
“…28, 29 When the free tubulin associates within the lattice defect, it is in the GTP form, in the straight conformation. 29 The healed site becomes mechanically and chemically more stable. 28, 29 A recent cellular study has shown that the healing of microtubules enhances the mechanical stability in cells.…”
Section: Non-equilibrium Aspects Of the Assembly Of Tubulin Into Micrmentioning
confidence: 99%